2003
DOI: 10.1128/aac.47.4.1291-1296.2003
|View full text |Cite|
|
Sign up to set email alerts
|

Engineering Anthracycline Biosynthesis toward Angucyclines

Abstract: The biosynthesis pathways of two anthracyclines, nogalamycin and aclacinomycin, were directed toward angucyclines by using an angucycline-specific cyclase, pgaF, isolated from a silent antibiotic biosynthesis gene cluster. Addition of pgaF to a gene cassette that harbored the early biosynthesis genes of nogalamycin resulted in the production of two known angucyclinone metabolites, rabelomycin and its precursor, UWM6. Substrate flexibility of pgaF was demonstrated by replacement of the nogalamycin minimal polyk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 21 publications
1
45
0
1
Order By: Relevance
“…Typische Primärprodukte der Typ-II-PKS aus der konzertierten Aktion von PKS, KR und Cyclasen sind Polyphenole, die in lineare Tetracycline, Anthracycline, Benzoisochromanchinone, Tetracenomycine, Aureolsäuren, Angucycline und pentanguläre Polyphenole untergliedert werden können. In manchen Fällen war es möglich, die Polyketid-Cyclisierung umzulenken, [88,89] es gibt allerdings anscheinend Designregeln oder spezielle Strukturbeschrän-kungen, die eine gewisse Inkompatibilität zwischen PKS-und Cyclase-Typen verursachen. [90] Es ist bemerkenswert, dass bakterielle Cyclasen sogar die Cyclisierung von Polyketiden, die durch (mutierte) Pilz-PKS produziert wurden, beeinflussen können.…”
Section: Steuerung Der Polyphenol-biosynthese Durch Typ-ii-pksmultienunclassified
“…Typische Primärprodukte der Typ-II-PKS aus der konzertierten Aktion von PKS, KR und Cyclasen sind Polyphenole, die in lineare Tetracycline, Anthracycline, Benzoisochromanchinone, Tetracenomycine, Aureolsäuren, Angucycline und pentanguläre Polyphenole untergliedert werden können. In manchen Fällen war es möglich, die Polyketid-Cyclisierung umzulenken, [88,89] es gibt allerdings anscheinend Designregeln oder spezielle Strukturbeschrän-kungen, die eine gewisse Inkompatibilität zwischen PKS-und Cyclase-Typen verursachen. [90] Es ist bemerkenswert, dass bakterielle Cyclasen sogar die Cyclisierung von Polyketiden, die durch (mutierte) Pilz-PKS produziert wurden, beeinflussen können.…”
Section: Steuerung Der Polyphenol-biosynthese Durch Typ-ii-pksmultienunclassified
“…The enzyme, functions like a chaperone, helping direct the nascent polyketide intermediates into particular reaction channels as well as catalyzing C-C bond formations (Hertweck et al 2007). In some cases, angucycline cyclase demonstrates flexibility for substrates, resulting in the formation of novel angucyclines in which an ethyl side chain is incorporated into the fourth ring of an anthracycline (Metsa-Ketela et al 2003). However, because of the difficulties in biochemical investigations of cyclases and their unstable substrates, the specific mechanism for these intriguing cofactor-free enzymes is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that 2 is formed through nonenzymatic conversion of 1 by oxidation and dehydration. [18,24,25] For instance, use of an absorbent such as XAD-7 in the cultivations, which conceivably protects the metabolites from oxidation, greatly enhances the production of 1. [18] In the coexpression experiment, addition of pgaE [a] The abbreviations used for the genes are as in Figure 1.…”
Section: Expression Of Post-pks Genes From the Pga Cluster In Streptomentioning
confidence: 99%
“…[15][16][17] The key element in the commitment of the pathway to angucyclic compounds is the action of a specific cyclase that closes the fourth ring and yields the first stable pathway intermediate: UWM6 (1, Scheme 1). [18,19] After this point the pathways diverge through the action of numerous tailoring or so-called post-PKS enzymes. In this context, oxygenases (OXY) play a key role in generating metabolic diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation